POLITICAL CORRUPTION IN INDIA ROLE OF CRIMINALS - RAJENDRAN, KUMAR; KUMAR , S. K. ASOK (International Journal of Psychosocial Rehabilitation, 2020)
The Constitution of India provides for elections based on adult franchise for the Central Legislature namely the Parliament and for the State Legislatures. The Representation of People Act was passed by the Parliament in 1951, to deal exclusively with the process of elections. After India got Independence, the first General Elections were held in 1952. Members of Parliament i.e., M.P.s and Members of Legislative Assemblies i.e., M.L.A.s for the State Legislatures are elected directly by the people. The President of India is elected indirectly by the people representatives, since India is a republic. Direct Democracy is not feasible here due to huge population. So, the elected representatives act on behalf of the people, but the Politicians who are governing as the ruling party, become very powerful as the governing class or the law makers. This enormous power act as a bait to the contestants who want to win elections by hook or crook. To achieve that, the help of criminals is taken by all the parties. Their muscle power and money power help the politicians to win power and in return the criminal elements do what they wish to do, affecting common man’s life and liberty. Criminals helping Political parties to win from outside or by entering the fray, hurts the process of democracy. This article analyses various criminal elements and mafia on politics and political life of the nation.